(untitled) (Journal of Philosophy Culture and Political Science, 2018)
This article characterizes traditionism spiritual and moral values of Confucian teachings and significance as a factor regulating social and political relations. The teachings of Confucius are studied in different countries as a philosophical system of ethical and aesthetic theory, political and social concept. In ancient Chinese philosophy the ethical doctrine of Confucius was associated with the development of society and social problems, so the author based on the research tries to reveal the meaning of the humanistic ethic-political doctrine of a thinker. The author shows the importance of the philosophical ideas of the Chinese thinker in the formation of the national mentality and social nature. Key words: Confucius, five principles of stability, moral and spiritual values, blessed man.